Traditional Herbal Medicine for Insomnia in Patients With Cancer: A Systematic Review and Meta-Analysis - Yoon, Jee-Hyun; Kim, Eun Hye; Park, Su Bin; Lee, Jee Young; Yoon, Seong Woo (Frontiers in Pharmacology, 2021)
Background: Insomnia is one of the most prevalent cancer-related symptoms and has a severe impact on the quality of life. This study aimed to evaluate the efficacy and safety of traditional herbal medicine (THM) for improving sleep quality in patients with cancer. Methods: Randomized controlled trials (RCTs) evaluating orally administered THM in a cancer population with insomnia were searched using nine electronic databases up to November 30, 2020. The outcome measurements were sleep quality measured by validated questionnaire such as the Pittsburgh Sleep Quality Index (PSQI), total effective rate, and adverse effects. The included studies were appraised using the Cochrane risk of bias tool and meta-analyzed. The quality of evidence was assessed using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) method. Results: Fourteen RCTs were included in the systematic review, and 10 RCTs were analyzed quantitatively. Compared to hypnotics, THM showed a significant improvement in sleep quality by reducing the PSQI score (mean difference [MD] -2.25, 95% confidence interval [CI] -3.46 to -1.05, I2 = 84%) and increasing the total effective rate (risk ratio [RR] 1.26, 95% CI 1.07 to 1.48, I2 = 70%) with low quality of evidence. Compared to placebo, THM also reduced the PSQI score significantly (MD -2.56, 95% CI -3.81 to -1.31, I2 = 91%) with moderate quality of evidence. The most frequently used herbs were Zizyphus jujuba Mill. No serious adverse events were observed. Conclusion: This review suggests that THM may be an effective therapeutic option for insomnia in patients with cancer. However, considering the limited methodological qualities and inconsistent results of the included trials, further rigorous RCTs are required.